Flows in Learning Theory (Behaviorisme, Cognitivisme and Constructivisme) - Ganesniko Sanjaya; Lestari Nur Fadhila; Kharisma Rahmawati; Eni Wahyuliani; Lathifah Nur’Aini; Aida Hayani (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2022)
Learning is an effort / effort to implement how humans learn, so that we can understand how the complex process of learning itself is. There are three learning theories that become the main perspectives, namely: behaviorism, cognitivism, and constructivism. Basically the 3 theories complement each other so that there is a main idea of its own. However, the most important thing of the three theories is how we understand which theory is good to implement in learning, this of course can improve the quality of learning. The research method is literature review or literature study, which contains theories relevant to research problems. The problem in this study is to find out how behaviorisme, Cognitivism and Constructivim in perspective of Education. In this section, an assessment of the concepts and theories used is carried out based on the available literature, especially from articles published in various scientific journals. The findings in this study are learning theory is the focus of attention on how one person can influence others so that the learning process occurs. And it turns out that there is a difference between learning theory and learning, Bruner revealed that learning theory can be defined as establishing a good learning method in order to obtain optimal learning outcomes. While the learning theory is called can be defined as a goal and explains how the learning process. From the theoretical study it can be concluded that in terms of the concepts of behaviorismis more the attitude or behavior of students, cognitivism is more knowledgeable about students and constructivism is more about building students' abilities.